Identification of the Potential of Infrastructure to Support Community Participation in the Development of the Lance Island Area - Marzuki, Farid Ahmad; Sidabutar, Yuanita FD; YM, Hardiyanti; Hayati, Nunung Nuring (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2024)
Lance Island, as the only island located in Tembesi Village, Sagulung District, Batam, has its challenges, especially in the provision and management of infrastructure in developing its area. This research aims to identify potential infrastructure that can increase the participation of the Lance Island community in the development of their region. This research analyzes existing infrastructure and identifies opportunities to develop better infrastructure obtained through field surveys, observations, interviews, and distributing questionnaires, using a qualitative descriptive analysis method approach which provides an overview of the situation of research results as well as quantitative analysis through regression analysis methods. multiple linear, with three independent variables in the form of electricity network infrastructure (X1), clean water network infrastructure (X2), and communal wastewater network infrastructure (X3), while the dependent variable is community participation (Y). The results of the variables of electricity network infrastructure, clean water network infrastructure, and communal wastewater network infrastructure as a whole significantly support community participation in the development of the Lance Island area and the results of this research can guide the government and stakeholders in increasing Lance Island's potential as a tourist village.